Pemberdayaan Masyarakat di Masa Covid-19 melalui Pelatihan Penanaman dengan Teknik Kokedama di Desa Pajagan Kabupaten Lebak Banten - Holilah Holilah (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The COVID-19 pandemic has an impact on the stability of the community’s economic welfare and the loss of job opportunities, many people are trying to find opportunities for entrepreneurship during this pandemic by utilizing waste into valuable goods. Kokedama is a planting technique from Japan that can replace the use of pots or can also be called the art of planting without pots,an alternative to indoor plants that have a high product selling value because they have a more attractive appearance. The purpose of this training is to provide skills to make kokedama to improve the economy of the Pajagan Village community, Lebak Banten Regency. The methods used in this training are the delivery of materials, the practice of making kokedama, and evaluation of training activities. Overall, the results of community responses to the material from this training activity stated that 100% of the training participants did not know KOkedama, 70% of participants were satisfied with the Kokedama training, and 60% of participants stated that the time used was quite efficient for training and practice. The skills that have been obtained are expected to improve the economy of the Pajagan Village community through planting ornamentall plants with the Kokedama technique by utilizing coconut fiber waste